2018
DOI: 10.21873/anticanres.13016
|View full text |Cite
|
Sign up to set email alerts
|

Relationship Between Postoperative CRP and Prognosis in Thoracic Esophageal Squamous Cell Carcinoma

Abstract: Background/Aim: Few studies have examined postoperative CRP in esophageal cancer. We investigated the relationship between postoperative CRP values according to the postoperative period and prognosis in esophageal cancer. Patients and Methods: We performed a retrospective cohort study including 187 patients who underwent esophagectomy for esophageal squamous cell carcinoma (ESCC) between January 2008 and October 2016. Results: CRP within 1 month of surgery was not related to overall survival (OS) or recurrence… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 17 publications
1
14
0
Order By: Relevance
“…It is well known that chronic inflammation plays a crucial role in the development and progression of malignant tumors and that CRP is an important indicator of inflammation (17,(33)(34). In the present study, the univariate analyses at the three time points showed that only serum CRP levels at the postoperative time point were positively associated with OS.…”
Section: Discussionsupporting
confidence: 50%
“…It is well known that chronic inflammation plays a crucial role in the development and progression of malignant tumors and that CRP is an important indicator of inflammation (17,(33)(34). In the present study, the univariate analyses at the three time points showed that only serum CRP levels at the postoperative time point were positively associated with OS.…”
Section: Discussionsupporting
confidence: 50%
“…Furthermore, researchers indicated that after multivariate adjustment post-operative high CRP concentration was an independent predictor for worse overall survival with HR = 2.23 (95% CI 1.44-3.47, p<0.001) [29]. A similar study was conducted by Katsurahara et al who examined 187 patients who underwent esophagectomy for esophageal squamous cell carcinoma [30]. Interestingly, CRP levels within the first month after surgery did not correlate with overall survival rate and recurrence-free survival rate.…”
Section: Crp In Follow-up After Endometrial Cancer Surgerymentioning
confidence: 87%
“…Interestingly, CRP levels within the first month after surgery did not correlate with overall survival rate and recurrence-free survival rate. CRP concentrations however, measured 2 months after the surgery show significant correlation with overall survival and recurrence-free survival, HR = 2.27 (95 % C 1.03-3.34, p=0.005) and HR = 1.65 (95 % CI 1.08-2.52, p=0.020) respectively [30]. The cut-off value for CRP concentrations was 1.5 mg/l, and the group with high CRP levels had significantly worse overall survival rate, 41.4 vs. 71.4 %, (p=0.0002) and recurrence-free survival rate RFS, 28.9 vs. 51.3 % (p=0.007) [30].…”
Section: Crp In Follow-up After Endometrial Cancer Surgerymentioning
confidence: 94%
See 2 more Smart Citations